Influência dos parâmetros de tratamentos térmicos de um aço maraging 350 - Silva, Jéssica Marinho Oliveira (2021)
Maraging steels combine ultra-high strength (1500 – 2450 MPa of tensile strength) with excellent toughness (50 – 240 MPa√) and are widely used in aerospace and military applications. Unlike other high strength steels hardened by reactions involving carbon, maraging steels achieve great hardness by the precipitation of intermetallic compounds of Ni, Mo and Ti on a soft martensitic matrix, during aging heat treatment. The exposure of these materials to extended times or excessive temperatures (overaging) leads to the excessive coarsening and growth of the precipitates and the partial reversion of the martensite to austenite, one of the equilibrium phases at room temperature. These reactions have great effect on the material’s mechanical properties, such as tensile strength, ductility and toughness, hence the comprehension of the phenomena which occur during heat treatment operations becomes extremely relevant. In the present work, the influence of the heat treatment’s parameters – solution treatment temperature, aging temperature and aging time – on the microstructure, hardness and martensite reversion was evaluated for a class 350 maraging steel. The austenite content of the samples was estimated by X-ray diffraction (XRD) technique, supported by ferritoscope results. Solution temperatures over 900 °C resulted in intense grain growth of the previous austenite, hardness reduction and reversed austenite content reduction. Aging at 600 °C for 12 h resulted in 40 % of reversed austenite, highest level amongst the conditions evaluated. Austenite reversion kinetics was proven to be dependent on aging temperature and time. Peak hardness – condition with hardness of 60 HRC and 5 % of reverted austenite – was achieved by aging at 480 °C for 5 h, with hardness retention level for at least 50 h of aging time. This behavior indicates the possibility of usage of a shorter thermal cycle than the commercially applied for this steel, as well as the potential application at this temperature for prolonged times without overaging